Waste Management Strategy at Alak Final Processing Site (TPA) in Realizing Sustainable Development Goals (SDGs) - Herly M.OEmatan; Minarni A. Dethan; Yemima Eka Christi Windya (CV. AFDIFAL MAJU BERKAH, 2023)
This research aims to evaluate existing waste management and formulate strategies for waste management that can be implemented used in realizing SDGs based on current conditions at the Alak Final Processing Site (TPA) which is the only TPA used to accommodate waste from all areas of the city of Kupang. The method used in this research is qualitative by conducting direct interviews and observations to collect data and information and then analyzed using the SWOT analysis tool to identify strengths, weaknesses, opportunities and threats. The results of the SWOT - IFAS analysis show that the strength factors get a total score of 1.6 and the weaknesses factors get a total score of 2.91 with a score difference of -1.31. This means that the weakness factor is greater than the strength factor. Meanwhile, the EFAS table shows that the opportunity factor gets a score of 2.34 and the threat factor gets a total score of 1.42 with a score difference of 0.92. This means that opportunities related to the development of TPA Alak can be maximized to reduce existing threats.